Analisis diseminasi perpustakaan di lingkungan TNI: studi pada Perpustakaan KODAM V/Brawijaya, Perpustakaan TNI Gatot Subroto dan Perpustakaan Dinas Sejarah Angkatan Laut pada tahun 2023 - Bahar, Nizam Zulfanuddin (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2025)
Theoretically, libraries are one of the key social instruments created by humans, playing a crucial role in the recording, management, and preservation of knowledge. As such, they are fundamental to the success and advancement of civilizations throughout history. Historical records show that following Indonesia’s War of Independence, the Armed Forces of the Republic of Indonesia (ABRI), particularly the Army, took on various roles across society—economically, socially, politically, and culturally. This continued until the Reform era, during which the Navy and Air Force eventually established their own libraries. From the author’s observations, this development has influenced how information dissemination is carried out by libraries under the TNI (Indonesian National Armed Forces), including how both internal and external stakeholders engage with them. This is the focus of the present study. Through qualitative approach—observation, interviews, and documentation—this research draws upon the analytical framework proposed by Indriyani (2021), which includes: (1) understanding and setting objectives, (2) identifying core messages, (3) understanding the audience, and (4) selecting appropriate media channels. The study finds that each military library has its own approach to information dissemination. When these practices are reflected against Law No. 43 of 2007 concerning Libraries, it is evident that all observed libraries are in compliance with its requirements. One important implication of this study is the potential to enrich the body of research concerning special libraries, particularly those operating in military contexts